Links between algorithms and textiles: experiments in fashion design - Pires, Marianna Ribeiro (2021)
This article aims to identify algorithmic applications in the area of fashion design, sincecurrently, the algorithms associated with automated procedures inherent to digital technologyare recognized. We also seek to understand its role in the composition of the creative workinvolved in fashion design, in addition to contributing to the search for creative solutions inproduct design. This research, in terms of its nature is applied, and as for its objectives, it isexploratory. The technical procedures used were the bibliographic research on the historyof the algorithms and their applications, in addition to experiments on manual creation oftextile textures developed based on algorithms. It is concluded that the use of algorithmsin the generation of textile textures is a creation tool that assists the process of the fashiondesigner, expanding the capacity of authorship and granting the character of manual artsin the design of fashion products.